The bifurcation theorem on the problem of thermal convection and contaminant transport in underground water - Can, Ngo Huy; Ha, Tran Thu (Vietnam Journal of Mechanics, 2000)
In the paper the bifurcation theorem on the problem of thermal convection and contaminant transport in underground water is proven.